Outcomes of lung transplantation for cystic fibrosis in a large UK cohort. Issue 8 (16th May 2008) - Meachery, G; De Soyza, A; Nicholson, A; Parry, G; Hasan, A; Tocewicz, K; Pillay, T; Clark, S; Lordan, J L; Schueler, S; Fisher, A J; Dark, J H; et al.
Abstract : Background: Lung transplantation is an important option to treat patients with advanced cystic fibrosis (CF) lung disease. The outcomes of a large UK cohort of CF lung transplantation recipients is reported. Methods: Retrospective review of case notes and transplantation databases. Results: 176 patients with CF underwent lung transplantation at our centre. The majority (168) had bilateral sequential lung transplantation. Median age at transplantation was 26 years. Diabetes was common pretransplantation (40%). Polymicrobial infection was common in individual recipients. A diverse range of pathogens were encountered, including the Burkholderia cepacia complex (BCC). The bronchial anastomotic complication rate was 2%. Pulmonary function (forced expiratory volume in 1 s % predicted) improved from a pretransplantation median of 0.8 l (21% predicted) to 2.95 l (78% predicted) at 1 year following transplantation. We noted an acute rejection rate of 41% within the first month. Our survival values were 82% survival at 1 year, 70% at 3 years, 62% at 5 years and 51% at 10 years. Patients with BCC infection had poorer outcomes and represented the majority of those who had a septic death. Data are presented on those free from these infections. Bronchiolitis obliterans syndrome (BOS) and sepsis were common causes of death. Freedom from BOS was 74% at 5 years and 38% at 10 years. Biochemical evidence of renal dysfunction was common although renal replacement was infrequently required (<5%). Conclusion: Lung transplantation is an important therapeutic option in patients with CF even in those with more complex microbiology. Good functional outcomes are noted although transplantation associated morbidities accrue with time.